PERBANDINGAN KELAS KATA BAHASA INDONESIA DENGAN BAHASA MELAYU THAILAND SELATAN - Muniroh Machu (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2021)
Comparison of Indonesian word classes with Southern Thai Malay language is a problem, namely how to compare Indonesian word classes with Southern Thai and Malay languages ​​so that there will be no errors in the use of said classes. The purpose of this study is to describe the similarities, differences and comparisons of Indonesian word classes with Southern Thai Malay. The type of research used in this study is a qualitative descriptive study. The results of the study are a comparison of Indonesian word classes with Southern Thai Malay language can be expressed in the same class of words, namely three word classes: Indonesian verbs with verbs Southern Thai Malay, Indonesian adjectives with the adjectives of South Thai Malay language and Indonesian verbs with language Southern Thai Malay. The difference between Indonesian words and Southern Thai Malay can be distinguished as noun, Pronomina and Numeralia words, adverb words can be found in Indonesian only, while South Thai Malay words can be classed as names.